Toward an integrative model of doping use: An empirical study with adolescent athletes - Lazuras, L.; Barkoukis, V.; Tsorbatzoudis, H. (Journal of Sport & Exercise Psychology, 2015)
The present study assessed adolescent athletes` intentions toward doping by using an integrative theoretical model. Overall, 650 adolescent athletes from team and individual sports completed an anonymous structured questionnaire including demographic information, social desirability, achievement goals, motivational regulations, sportspersonship orientations, social cognitive variables, and anticipated regret. Hierarchical regression analysis showed that the integrative model predicted 57.2% of the variance in doping intentions. Social cognitive variables and anticipated regret directly predicted doping intentions. Anticipated regret added 3% incremental variance on top of other predictors. Multiple mediation analyses showed that the effects of achievement goals on intentions were mediated by self-efficacy beliefs, whereas the effects of sportspersonship were mediated by attitudes and anticipated regret. The present study confirmed the dual structure of an integrative model of doping intentions and further highlighted the role of anticipated regret in the study of adolescent doping use.